Analysis of The Use of Equivalent Compound Sentences and Multiple Compound Sentences in News Published by Tanjungpinang Pos - Ajeng Putri Larasati; Suhardi; Siti Habiba (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the use of equivalent compound sentences and multilevel compound sentences and describe the semantic relationship between clauses of equivalent compound sentences and multilevel compound sentences in news published by Tanjungpinang Pos. The object of this research is news published by Tanjungpinang Pos. The research method uses a qualitative approach with a qualitative descriptive research type. The data collection technique used is the document technique. The data analysis technique was carried out using content analysis techniques. The results of this research are based on data on the use of equivalent compound sentences and multilevel compound sentences in news published by Tanjungpinang Pos, 16 data were found, namely 8 data of equivalent compound sentences and 8 data of multilevel compound sentences. These 8 data of equivalent compound sentences are divided into 1 data which is included in the semantic relationship between clauses seen from the meaning of the clauses being connected, 7 data which is included in the semantic relationship between clauses of a compound sentence which is equivalent to an addition relationship, while the semantic relationship between clauses of a compound sentence is 8 data levels. These 8 data are divided into 4 data which are included in the semantic relationship between clauses of multi-level compound sentences, causal relationships, 3 data which are included in the semantic relationships between clauses of multi-level compound sentences, which are goal relationships, and 1 data which is included in the semantic relationships between clauses of multi-level compound sentences, which are results relationships.